Can you feel it? - Lomme, Freek ca. 20. Jh; Bekirović, Semâ 1977- (Onomatopee, 2016)
What exactly is the tactile, in a world in which a rising technocracy exploits the designed environment we feel? Who authorises and who writes, what tradition do we stand in and how can we touch base? Presenting artists in the practice of making and thinkers in the development of thought here and now, we connect to tactile characteristics, guided by a specific focus on graphic, printed matter.